Maximizing project value : defining, managing, and measuring for optimal return - Berman, Jeff, 1966- (Amacom, American Management Association, 2007)
"Maximizing Project Value shows you how to put the emphasis on value when managing a project, from the project's initial inception, all the way through its completion and even farther down the road to determine whether it's of continuous worth to the company. This guide offers a step-by-step plan you can use to establish the value of a project, identify value drivers and key performance metrics and then track and report them, organize a team for accountability, and much more."--Jacket.